Pembinaan dan Layanan Kecakapan Hidup Peserta Didik di MAN Purbalingga - Atthamimy, Alfam (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
Coaching students is part of the management of students which requires madrasas to not just take notes - record the administration of students. Coaching students can be actualized by the existence of activities that accommodate all the needs of students in the field of self-potential development and increase their knowledge. Madrasas need to provide guidance to students through activities that are deemed necessary. It is necessary in the sense of providing benefits for students, for madrassas and the community. The study in this paper is to determine the coaching and life skills services of students at MAN Purbalingga.The results of this study are 1) MAN Purbalingga seeks to establish itself as a research madrasa, through research-based activities carried out by MAN Purbalingga students and / or teachers; 2) Coaching students in MAN Purbalingga is carried out through various activities not only to accommodate talents and interests but also in order to grow and develop life skills of students both academic, personal, social and vocational; 3) the activities of fostering students in MAN Purbalingga consist of guidance on character of noble and religious character, guidance on subjects and the Olympics, guidance on institution management, education and training in journalism and research, as well as through intracuricular and extracurricular activities; 4) Services provided to students include: library, canteen, school health unit, guidance and counseling, vehicle parking, worship facilities and other learning support facilities.